Xuanzang’s Theory “Transliteration for Five Occasions” In Religious and Cultural Loanwords Translation - Shen, Huijia (International Journal of Humanities and Education Development (IJHED), 2022)
Monk Xuanzang, a great translator in the Tang Dynasty in China, once put forward the famous Buddhist sutra translation theory of “transliteration for five occasions”, that is, transliteration for mystery, for polysemy, for non-existence, for following the past and for respect. This article explains the connotation and limits of this theory, and comprehensively reveals its guiding role in the translation of religious and cultural loanwords as well as the important role in promoting the development of Chinese translation theory.